Influential Factors Shaping the Behavioral Intention of Undergraduate Students towards Livestream Shopping in Chengdu, China - Yuan, Yizhen (Scholar: Human Sciences, 2025)
Purpose: This study intends to investigate the factors influencing the choice of live shopping among students in Chengdu. The study explores the relationship between seven variables: perceived ease of use, perceived usefulness, perceived enjoyment, attitude, service quality, social influence, and behavioral intention. Research design, data, and methodology: The researcher used the quantitative method (n=500) to distribute questionnaires to undergraduate students in three designated universities in Chengdu. Considering the principle of similarity in geographical location and representativeness at the school level, the judgmental sampling was to select three universities. Quota sampling fixes the number, and convenience sampling helps with the data collection and distribution of surveys in multiple ways. The Structural Equation Model (SEM) and Confirmatory Factor Analysis (CFA) were used for the data analysis, and they included model fit, reliability, and validity of the constructs. Results: The results explicated that perceived ease of use, usefulness, and enjoyment significantly impact attitude. Moreover, attitude, service quality, and social influence significantly affect behavioral intention. Conclusions: All hypotheses were completely proven to fulfill research objectives. Hence, there is a need to continuously develop new technologies and improve the quality and level of service to meet consumers’ different needs and tastes.